Participation in microfinance scheme: a medium for empowering community with special reference to Nigeria - Saidu, Mohammed Bashir; Abu Samah, Asnarulkhadi; Redzuan, Ma'rof; Ahmad, Nobaya (Marsland Press, 2014)
For the past three decades, microfinance scheme has become a key instrument for community empowerment in developing countries. In recent years the scheme has attracted international attention thereby assuming a prominent place in community development discourse. This paper discusses the role of microfinance scheme as a tool for community empowerment in Nigeria. Previous literature revealed that successive Nigerian governments in the past initiated a series of public financed programs and policies targeted at the poor but unfortunately, all those programs have failed to deliver. The current Nigerian government‟s policy on National Economic Empowerment Development Strategy (NEEDS) where microfinance scheme is identified as one of the key instrument for empowerment is reviewed and discussed along the bottom-up principles. Lastly, this paper proposed a model of framework for microfinance in Nigerian context.